Optimization of snap fit features design for rapid prototyping fabrication / Mohd Amiruddin Adnan - Adnan, Mohd Amiruddin (2010)
Introduction of elastic integral mechanical interlock on product design take an advantage in eliminating miscellaneous parts. In other word, cost and time reduction can be made by simplification unwanted parts. The elastic integral mechanical interlock or known as Snap-fit can be divided into several types. Namely cantilever beam, annular snap, compression hook and etc. Snap-fit extensively applied in automotive parts, electronic devices, biomedical apparatus and toys. The main goal of this study is to determine the most favorable snap fit design so that it can working successfully depend on specified task. In order to achieve the above objective, snap-fit design optimization has to be accomplished before it can be implemented to a particular design. However, this study will just focus on cantilever snap fit. The performance of the snap fit will be determined by manipulating certain parameter to generate the insertion and retention force. The testing also will determine the allowable deflection of the snap fit when the part is joining together with the mating part. For testing purpose, special jig was design, fabricate and attached at Instron Machine. The specimens for testing were fabricated using Rapid Prototyping (RP) which using multi-jet technology (MJM). Before the parts are fabricated using RP, the design will be done using CATIA V5 and will be repair using Magics software in STL format. From tensile test result, it shows that the material will become weaker when exposed to environment. The surface roughness on top and bottom surface on specimens is different. Dimensional accuracy test indicates that there are shrinkage occur on specimens. For snap fit testing, fillet and taper will provide robustness characteristics to the snap fit.